Personalized Injury Reduction Strategies in Sports Medicine: Lessons Learned from Advances in Breast Cancer Treatment: A Clinical Commentary - Garrett Bullock; Gary Collins; Rober Adams; Charles Thigpen; Ellen Shanley (International Journal of Sports Physical Therapy)
# Background